Short‐term and long‐term outcomes of revascularization interventions for patients with severely reduced left ventricular ejection fraction: a meta‐analysis. (3rd December 2020) - Pei, Junyu; Wang, Xiaopu; Xing, Zhenhua; Zheng, Keyang; Hu, Xinqun
Abstract: Aims: This meta‐analysis aimed to determine whether coronary artery bypass grafting (CABG) or percutaneous coronary intervention (PCI) should be preferred in patients with severely reduced left ventricular (LV) ejection fraction. Methods and results: We searched the PubMed, EMBASE, and Cochrane Library databases from the conception of the databases till 1 May 2020 for studies on patients with severely reduced LV ejection fraction undergoing CABG and PCI. The primary clinical endpoints were 30 day and long‐term mortalities. The secondary endpoints were 30 day and long‐term incidences of myocardial infarction (MI) and stroke, long‐term cardiovascular mortality, and repeat revascularization. Eighteen studies involving 11 686 patients were analysed. Compared with PCI, CABG had lower long‐term mortality [hazard ratio (HR): 0.70, 95% confidence interval (CI): 0.61–0.80, P  < 0.01], cardiovascular mortality (HR: 0.60, 95% CI: 0.43–0.85, P  < 0.01), MI (HR: 0.51, 95% CI: 0.36–0.72, P  < 0.01), and repeat revascularization (HR: 0.32, 95% CI: 0.23–0.47, P  < 0.01) risk. Significant differences were not observed for long‐term stroke (HR: 1.18, 95% CI: 0.74–1.87, P  = 0.49), 30 day mortality (HR: 1.18, 95% CI: 0.89–1.56, P  = 0.25), and MI (HR: 0.42, 95% CI: 0.16–1.11, P  = 0.08) risk. CABG was associated with a higher risk of stroke within 30 days (HR: 2.88, 95% CI: 1.07–7.77, P  = 0.04). In a subgroup analysis of propensity score‐matched studies, CABG was associated with a higher long‐term risk of stroke (HR: 1.61, 95% CI: 1.20–2.16, P  < 0.01). Conclusions: Among patients with severely reduced LV ejection fraction, CABG resulted in a lower mortality rate and an increased risk of stroke.